AFTERWORD: PUBLIC SECTOR ANTHROPOLOGISTS AND NEW DIRECTIONS FOR A PUBLIC ANTHROPOLOGY. Issue 2 (November 2013) - Ono, Sarah S.; Solimeo, Samantha L.; Besterman‐Dahan, Karen; Hamilton, Alison
<x xml:space="preserve">Abstract</x> In this final contribution in the edited volume on anthropologists working in the Veterans Health Administration within the Department of Veterans Affairs (VA), the authors reflect on how developments in recent years have brought us to this moment in time from the "insider" perspective of VA anthropologists. These collected papers provide ethnographic evidence for the innovative ways in which anthropologists employed in the public sector constitute a public anthropology that is theoretically informed, actionable, and cognizant of its role in the production of authoritative knowledge. The "afterword" makes connections between the chapters, with their varied topics, and addresses how this volume points to new destinations for engaged and ethical research in the growing field of public sector anthropology.